Intravenous Delivery of Targeted Liposomes to Amyloid-β Pathology in APP/PSEN1 Transgenic Mice - Tanifum, Eric A. (Public Library of Science, 2012)
Extracellular amyloid-β (Aβ) plaques and intracellular neurofibrillary tangles constitute the major neuropathological hallmarks of Alzheimer’s disease (AD). It is now apparent that parenchymal Aβ plaque deposition precedes behavioral signs of disease by several years. The development of agents that can target these plaques may be useful as diagnostic or therapeutic tools. In this study, we synthesized an Aβ-targeted lipid conjugate, incorporated it in stealth liposomal nanoparticles and tested their ability to bind amyloid plaque deposits in an AD mouse model. The results show that the particles maintain binding profiles to synthetic Aβ aggregates comparable to the free ligand, and selectively bind Aβ plaque deposits in brain tissue sections of an AD mouse model (APP/PSEN1 transgenic mice) with high efficiency. When administered intravenously, these long circulating nanoparticles appear to cross the blood-brain barrier and bind to Aβ plaque deposits, labeling parenchymal amyloid deposits and vascular amyloid characteristic of cerebral amyloid angiopathy.